PENGUASAAN BAHASA PERTAMA PADA ANAK TRANSMIGRAN ASAL JAWA DI AIR HAJI PESISIR SELATAN SUMATERA BARAT - Noviarini, Tiara (JURNAL PESONA, 2018)
Language acquisition in children is influenced by the social and environmental conditions of parents. Environmental parents referred to here is the emotional state and education level of parents, both of these can affect a childs first language acquisition because the parents who become real examples imitated by children receive and develop the stimulus provided by the environment. The first language is often pronounced by ordinary children in the form of the local language or mother tongue, whether it would also be the same as the children grow and develop in a foreign environment. In this study, we wanted to show the first variant of the use of language in children Transmigrans Javanese residence and domicile in Air Haji, Pesisir Selatan, Sumatra Barat. This study will focus on the acquisition of the first child and how they can receive the stimulus is passed from parents or from their social environment play? Collecting data in this study using descriptive qualitative method. The results of this study indicate that the first language they know is the Java language with Minang accent. Because their parents are still thick with the use of the Java language, but the Java language level minang rough.